Merancang Strategi Kreatif Produksi Iklan Layanan Masyarakat dalam Menyampaikan Pesan Sosial - Kurnia, Ari; Saragih, Ruth Putryani; Jessica, Miranda (Indonesian Journal for Social Responsibility, 2025)
Public Service Announcement (PSAs) are often rigid and seem serious because they aim to shape behavioral changes, both for individuals, groups and their social order. The ILM production process is the same as advertising production in general, but the output produced in PSA is not in the form of profit. PSA in social marketing requires a creative strategy in compiling messages and placing PSA media so that it is more able to encourage consumers to change behavior. Through this Community Service activity, creativity can also be expressed in PSA production which is built through various methods such as the courage to take risks, the courage to challenge assumptions, the courage to take opportunities for change and the ability to see in new ways. Community Service participants are students in grades X and XI at SMK Fransiskus 1 Jakarta, and collaborate with active students of the Bakrie University Communication Science Study Program, using the lecture method and Project Based Learning (PjBL) through audio-visual production training and public speaking provided by the Community Service Team and TVOne Senior Presenter, Indy Rahmawati. Furthermore, participants make PSA videos with topics related to the SDGs. The purpose of this activity is to provide an understanding of how creative strategies in making PSAs to convey persuasive messages and media placement as a social marketing medium. The results of this activity, participants know the characteristics of commercial advertising with PSAs and how to design creativity in PSAs production and delivery with good public speaking.